The Impact of Financial Management Practices on the Growth of Small and Medium Enterprises (SMEs) in Makassar - Khair, Muhammad Miftahul; Salle, Ilham Z.; Limoa, William S.; Yuliana, Leny (Scieclouds Publishing, 2025)
This study examines the impact of financial management practices on the growth of Small and Medium Enterprises (SMEs) in Makassar using a quantitative research design. Data were collected from 180 SMEs across diverse sectors, including retail, manufacturing, agriculture, and services, through structured questionnaires. The study focused on four key financial management practices: financial record-keeping, budgeting, financial planning, and cash flow management, measured alongside SME growth indicators such as revenue, profitability, employee expansion, and market reach. Multiple regression analysis revealed that financial management practices collectively explained 72% of the variance in SME growth, with financial record-keeping (Beta = 0.46) emerging as the most influential factor. Budgeting (Beta = 0.38), financial planning (Beta = 0.36), and cash flow management (Beta = 0.33) also significantly contributed to growth, highlighting the importance of these practices in ensuring business sustainability and expansion. This research addresses a notable gap in existing literature by providing localized insights into SME financial management practices in a developing economy context and quantifying their impact. The findings emphasize the synergistic effect of integrating these practices and underscore the need for targeted training and policy interventions to enhance financial literacy and resource accessibility for SMEs in Makassar. These results offer actionable recommendations for SME owners, policymakers, and researchers aiming to foster sustainable business growth in similar environments.